2021
DOI: 10.3390/d13100457
|View full text |Cite
|
Sign up to set email alerts
|

A Mysterious World Revealed: Larval-Adult Matching of Deep-Sea Shrimps from the Gulf of Mexico

Abstract: The identification of deep-sea (>200 m) pelagic larvae is extremely challenging due to the morphological diversity across ontogeny and duration of larval phases. Within Decapoda, developmental stages often differ conspicuously from their adult form, representing a bizarre and mysterious world still left to be discovered. The difficulties with sampling and rearing deep-sea larvae, combined with the lack of taxonomic expertise, argues for the use of molecular methods to aid in identification. Here, we use DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…The transportation could also occur during the larval phases (Shanks 2009). Little is known about deep-sea pelagic larvae, especially the total number of larval phases of a determined species and the morphological variations along the multiple stages (Varela and Bracken-Grissom 2021 b ). The only description of a gravid P. microphthalma female indicated three large eggs attached to the female’s pleopods (Foxton and Herring 1970).…”
Section: Discussionmentioning
confidence: 99%
“…The transportation could also occur during the larval phases (Shanks 2009). Little is known about deep-sea pelagic larvae, especially the total number of larval phases of a determined species and the morphological variations along the multiple stages (Varela and Bracken-Grissom 2021 b ). The only description of a gravid P. microphthalma female indicated three large eggs attached to the female’s pleopods (Foxton and Herring 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Another constraint is the limited morphological characteristic of the crustacean larvae that can easily be used to diagnose the various crustacean species (Haug et al 2016). DNA barcoding has successfully solved these constraints using a short fragment of the cytochrome c oxidase 1 (COI) gene (Brando et al 2016;Rahman et al 2019;Palecanda et al 2020;Varela and Bracken-Grissom 2021). Several studies showed that the gene is a reliable barcode for crustacean barcoding (Raupah and Radulovici 2015;Matelatto et al 2016;Bhagawati et al 2020), including crustacean larvae (Palecanda et al 2020;Kusbiyanto et al 2020).…”
Section: Introductionmentioning
confidence: 99%